OC-087 Randomised trial of enteral feeding in patients discharged from hospital following surgical resection of an upper gastrointestinal malignancy. (22nd June 2015) - Froghi, F; Sanders, G; Wheatley, T; Berrisford, R; Peyser, P; Rahamim, J; Lewis, S
Abstract : Introduction: Patients undergoing upper gastrointestinal surgery often eat poorly post operatively, despite dietetic input. The benefit of nutritional supplementation following hospital discharge is unknown. We examined the benefit of 6 weeks nutritional supplementation via the patients feeding jejunostomy on fatigue, quality of life and independent living. Method: Patients undergoing oesophagectomy or total gastrectomy for cancer had a feeding jejunostomy placed routinely at surgery. Jejunal feeding was started postoperatively and if tolerated at discharge consenting patients were randomly allocated (stratified by gastric/oesophageal) to nutritional supplementation (600 Kcal/day) via their feeding jejunostomies or no jejunal supplement. All patients received oral supplements and dietetic input. Patients were assessed at discharge and 3, 6, 12 and 24 weeks following discharge for fatigue (MFI-20), quality of life (EORTC QLQ-OES18), health economic analysis (independent living: EQ5D) as well as completing 2 day dietary diaries. Results were analysed non-parametrically (Mann-Whitney) and data presented as medians with interquartile ranges. Results: 44 patients (M:F 29:15) were randomised, 23 received jejunal supplements. There was no difference between the groups in age, sex, neo-adjuvant chemotherapy, ASA grade, type of operation, operative time, blood loss, length of hospital stay, and inpatient complications. Percentage of calculated energy requirement actually received was greater in the supplemented group at weeks 3 and 6 (p < 0.0001). Jejunal supplementation did not suppress oral energy intake. There was no difference between the two groups for oral energy intake at any time period. No complications were seen from jejunal feeding in the community. After hospital discharge, scores for MFI-20, EQ5D and EORTC QLQ-OES18 were not different between groups at any time point. From hospital discharge fatigue improved and plateaued at 6 weeks (p < 0.05 for both groups), independence at 12 weeks (p < 0.05 for both groups) but no improvement was seen in quality of life until 24 week in the active group alone (p < 0.02) and not at all in the control group. Conclusion: Dietary intake following hospital discharge after oesophageal or gastric surgery is poor. Addition of jejunal feeding over and above dietary advice and sip feeds is effective in providing patients with an adequate energy intake. Increased energy intake however, produced no obvious improvement in measures of fatigue, quality of life or health economics. Interestingly improvement in fatigue and independence plateaued by 12 weeks whilst there was little evidence of improvement in quality of life at 24 week. Disclosure of interest: None Declared.